Poškodbe starostnikov - Herman, Simon (Zdravniški vestnik, 2008)
Injured old people are difficult surgical patients. Thatćs true not because ofneed for advanced surgery, but because of everything else: preparation for surgery, hospital care and rehabilitation. For good results is of paramount importance a good organized healthcare system and good result can be seen in every patient who returns to autonomous life can after treatment.
Keywords: Aged; Femoral Fractures; Femur, zlomi; poškodbe; Radius Fractures; Radius, zlomi; Rane in poškodbe; Rehabilitation; Starostniki; Surgery; Wounds And Injuries; zdravstveno varstvo